2021
DOI: 10.1038/s41598-021-90797-0
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of the CD80/86 proinflammatory axis as a therapeutic strategy to prevent severe COVID-19

Abstract: An excessive immune response known as cytokine storm is the hallmark of severe COVID-19. The cause of this cytokine rampage is yet not known. Based on recent epidemiological evidence, we hypothesized that CD80/86 signaling is essential for this hyperinflammation, and that blocking this proinflammatory axis could be an effective therapeutic approach to protect against severe COVID-19. Here we provide exploratory evidence that abatacept, a drug that blocks CD80/86 co-stimulation, produces changes at the systemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Its activity in modulating T-cell activation and downregulating cytokines production while monitoring the downstream immune response has drawn interest in considering it as a drug for COVID-19 [ 45 ]. Systemic response of abatacept also showed high significant antagonism with COVID-19 severity, further supporting the use of abatacept to prevent severe COVID-19 [ 46 ]. Furthermore, a phase 3 ACTIV-1 Immune Modulators trial involving 1022 patients showed that a 10 mg/kg dose of abatacept administration reduced the mortality rate by 37.4%.…”
Section: Current Approaches To Finding Covid-19 Treatmentmentioning
confidence: 78%
“…Its activity in modulating T-cell activation and downregulating cytokines production while monitoring the downstream immune response has drawn interest in considering it as a drug for COVID-19 [ 45 ]. Systemic response of abatacept also showed high significant antagonism with COVID-19 severity, further supporting the use of abatacept to prevent severe COVID-19 [ 46 ]. Furthermore, a phase 3 ACTIV-1 Immune Modulators trial involving 1022 patients showed that a 10 mg/kg dose of abatacept administration reduced the mortality rate by 37.4%.…”
Section: Current Approaches To Finding Covid-19 Treatmentmentioning
confidence: 78%
“…AURKB controls cell cycle progression and proper chromosome segregation, and may play a role in SARS CoV-2 nucleocapsid phosphoprotein (N-protein) mutation since important Aurora kinase B phosphorylation sites (R203 and G204) are commonly mutated residues of N-protein [54,73]. TYMS is involved in the CD80/86 proinflammatory axis, and is upregulated in severe COVID-19 patients [74]. Dysregulation of this gene pathway may contribute to downstream effects of antigen presentation and sustained T cell activation [75].…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggested that abatacept was a potential strategy for severe COVID-19 based on the intersection of DEGs, the resemblance of antirheumatoid mechanisms and immune-inflammatory responses in COVID-19. Abatacept treatment could be a critical way to avoid an inflammatory storm in COVID-19 ( 13 ). Compared with the study of Julia et al, we conducted an analysis using larger sample size, identified potential biomarkers, and explored deeper mechanisms through which abatacept treats CODVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Drug repurposing is a strategy for identifying new indications for approval. Evidence has been provided for abatacept as a candidate therapeutic approach to prevent severe COVID-19 ( 13 ). However, the mechanism of abatacept acting on COVID-19 remains unclear.…”
Section: Introductionmentioning
confidence: 99%